2013
DOI: 10.1614/ipsm-d-12-00061.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Biomass and Starch Allocation of Common Reed (Phragmites australis) (Haplotype I) in Southern Alabama, USA

Abstract: Common reed (Phragmites australis) is a nonnative invasive perennial grass that is problematic in aquatic and riparian environments across the United States. Common reed often forms monotypic stands that displace native vegetation which provide food and cover for wildlife. To help maintain native habitats and manage populations of common reed in the United States, an understanding of its life history and starch allocation patterns are needed. Monthly biomass samples were harvested from sites throughout the Mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In addition to the hypoxic conditions that are prevailing in the endosperm that appear to be conducive to starch synthesis, some aquatic members of the Poaceae, such as the common cattail or bulrush (Typha latifolia L.), and the common reed (Phragmites australis Cav.) produce large quantities (~70% by weight) of storage starch in their submerged rhizomes [127,128] under highly hypoxic conditions. Mutations in key steps in the provision of carbon for ADP-Glc formation outlined above, namely, miniature 1 (min1) for INV, shrunken 1 (sh1) for SuSy, and either shrunken 2 or brittle 2 (sh2 or bt2) for AGPase, underline the importance of cytosolic ADP-Glc as a precursor for storage starch synthesis in the endosperms of the Poaceae [98,109,129,130].…”
Section: Provision Of Carbon To the Endospermmentioning
confidence: 99%
“…In addition to the hypoxic conditions that are prevailing in the endosperm that appear to be conducive to starch synthesis, some aquatic members of the Poaceae, such as the common cattail or bulrush (Typha latifolia L.), and the common reed (Phragmites australis Cav.) produce large quantities (~70% by weight) of storage starch in their submerged rhizomes [127,128] under highly hypoxic conditions. Mutations in key steps in the provision of carbon for ADP-Glc formation outlined above, namely, miniature 1 (min1) for INV, shrunken 1 (sh1) for SuSy, and either shrunken 2 or brittle 2 (sh2 or bt2) for AGPase, underline the importance of cytosolic ADP-Glc as a precursor for storage starch synthesis in the endosperms of the Poaceae [98,109,129,130].…”
Section: Provision Of Carbon To the Endospermmentioning
confidence: 99%
“…In the fall, P. australis resources are translocated from above-ground tissue into rhizomes, and are allocated to new growth in the spring (Juneau and Tarasoff, 2013). The primary storage carbohydrate is starch (Mal and Narine, 2004), which comprises 1 -10% of above-ground biomass and 5 -20% is stored in below-ground biomass (Wersal et al, 2013). Rhizomes that undergo overwintering receive carbohydrates from shoots to encourage growth when the growing season returns (Boar, 1996;Wersal et al, 2013), and it follows that rhizomes collected for greenhouse experiments in the fall have higher survivorship than those collected in the spring (Juneau and Tarasoff, 2013).…”
Section: Vegetative Reproduction Spread and Patch Dynamicsmentioning
confidence: 99%
“…The primary storage carbohydrate is starch (Mal and Narine, 2004), which comprises 1 -10% of above-ground biomass and 5 -20% is stored in below-ground biomass (Wersal et al, 2013). Rhizomes that undergo overwintering receive carbohydrates from shoots to encourage growth when the growing season returns (Boar, 1996;Wersal et al, 2013), and it follows that rhizomes collected for greenhouse experiments in the fall have higher survivorship than those collected in the spring (Juneau and Tarasoff, 2013). Rhizomes allow P. australis to allocate resources to young shoots to achieve a stand structure with more uniform shoot height and weight (Hara et al, 1993).…”
Section: Vegetative Reproduction Spread and Patch Dynamicsmentioning
confidence: 99%
“…A physiological weak point in the life cycle of a plant is when it is least likely to recover from the application of a control method (Luu and Getsinger 1990a). Many studies have determined the physiological weak points within the life cycle of many macrophyte species based primarily on seasonal carbohydrate allocation patterns and have demonstrated that timing the control approach to the target species' weak point in carbohydrate storage can improve the effectiveness of control (Madsen 1993a(Madsen , 1997Katovich et al 1998;Madsen and Owens 1998;Owens and Madsen 1998;Woolf and Madsen 2003;Wersal et al 2011;Wersal, Madsen, and Cheshier 2013;Eid and Shaltout 2016).…”
Section: Introductionmentioning
confidence: 99%